PERSPEKTIF MAHASISWA BERLATAR JURUSAN KEISLAMAN TERHADAP PEMBELAJARAN BAHASA INGGRIS - Qori’ah Maghfirotillah (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2015)
This research’s goal is to know the perspective of Islamic studies students towards English learning process. For reaching this goal, there are two research questions: 1) what is the perspective of Islamic studies students towards English learning process in State Islamic University of Sunan Ampel Surabaya? 2) how does English learning process help Islamic studies students in State Islamic University of Sunan Ampel Surabaya to enrich their field study knowledge?. Mixed method was chosen as the method to collect and analysis the data. To answers the first research question, survey was used as research method, and questioner was used as instrument. There were 10 statements in the questioners that were given to 100 participants. Meanwhile, to answer the second research question, qualitative approach was chosen as method to gain answer. Interview was used as data collecting technique that involved 25 participants as informant. Finally, it was found that Islamic studies students had positive perception dealing with the importance of learning English. The result also showed that English learning process on most of students’ perspective had not been effective and it did not give much contribution in increasing students’ English ability which deals with their disciplines. In conclusion, positive perception of students about the importance of learning English was not facilitated enough by learning process.